Effectiveness of the Public Health Emergency Operation Center (Pheoc) in the Context of Coronavirus Disease 2019 at the Provincial Level - ขิงจัตุรัส, ณัฐนรี; คงศีล, สุุคนธา; เจียมตน, สุขุม; อินทรประสงค์, ภูษิตา; เวชภัณฑ์เภสัช, สุภโชค (Journal of Health Science of Thailand, 2024)
This research aimed to evaluate the effectiveness of the PHEOC for COVID-19 at the provincial level, analyse the associate, and explain the variations between personnel characteristics, organizational characteristics, management policies and practices, and environmental characteristics at the provincial level. Data were collected by using questionnaires developed based on the concepts of Steers and Mott. The samples were 53 provincial public health offices selected by stratified random sampling. They were the chief or deputy chief of the provincial public health office, the head of the communicable disease control group, and the head of the strategic development group, with a total of 159 informants. The data were analyzed using descriptive statistics, Pearson product-moment correlation, and multiple regression analysis. It was found that the overall effectiveness of the PHEOC for COVID-19 was highly significant (Mean=3.89, SD=0.50). It was observed that all four factors had a moderately positive correlation with the effectiveness of the PHEOC for COVID-19, with personnel characteristics (r=0.64), organizational characteristics (r=0.64), policy and operation (r=0.68), and environmental characteristics (r=0.70) all showing statistically significant relationships (p<0.01). Moreover, personnel characteristics, environmental characteristics, and policy and operation collectively account for 57.8% of the variance in the effectiveness of the PHEOC for COVID-19 at the provincial level. The inability to explain the variability of the performance of PHEOC might stem from the fact that commanders at each center define the organizational structure, roles, authority, and operational procedures according to the templates provided by the Ministry of Public Health. This resulted in minimal variation in the organizational characteristics of PHEOC across provinces. Consequently, organizational characteristics emerged as the least influential factor on performance. This research could be utilized to enhance provincial PHEOC, which might involve formulating policies to strengthen organizational commitment, ensuring that all systems and processes within the organization are aligned, and implementing SMART PHEOC policies focused on digital system development, digital skill enhancement for personnel, cybersecurity, and quality management.